Pendidikan Karakter melalui Penanaman Etika Berkomunikasi dalam al-Qurâan - Mudlofir, Ali (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
The study is aimed at exploring the Qurâanic concept of education. It argues that the Qurâan mostly speaks of education in terms of character-building and tries to inculcate noble values upon human being in such a way that the good characters may be attained. Hence, the paper is of an argument that the Qurâanic concept of education is ethical; it imposes ethical values upon human being. But the aspect of ethics that the paper will be speaking is that which has to do with ethics in social interaction. The paper will look at some key terms that the Qurâan uses to infer to this social interaction which include qaulan sadida, qaulan maârufa, qaulan baligha, qaulan masysura, qaulan karima, and qaulan layyina. To offer a better explanation of what social interaction is all about, the paper will address and invoke some social setting in which people interact one another. In other words, the argument of the paper will be invalidated by the social facts found on the ground. This study is thus both normative and empirical.